Knockdown of vascular cell adhesion molecule 1 impedes transforming growth factor beta 1-mediated proliferation, migration, and invasion of endometriotic cyst stromal cells - Juan Zhang; Hui Li; Dan Yi; Chuntian Lai; Haiyan Wang; Wenda Zou; Bei Cao (BMC, 2019)
Abstract Purpose Endometriosis is one of the most common, difficult, and complicated gynecological disorders. Vascular cell adhesion molecule 1 (VCAM-1) has been reported to be aberrantly expressed in patients with endometriosis. However, the exact role and mechanism of VCAM-1 in endometriosis remains unclear. Methods The expression of transforming growth factor beta 1 (TGF-β1) and VCAM-1 was determined by quantitative real-time polymerase chain reaction and western blotting. Human endometriotic cells were cultured and their responsiveness to TGF-β1 was evaluated by Cell Counting Kit-8, 5-ethynyl-2'-deoxyuridine, and transwell migration and invasion assays. Results The levels of TGF-β1 and VCAM-1 mRNA were upregulated in the endometriotic tissues. Knockdown of TGF-β1 in endometriotic cyst stromal cells caused a marked inhibition of cell proliferation, migration, and invasion. Treatment of endometriotic cyst stromal cells with TGF-β1 resulted in an obvious promotion of cell proliferation, migration, and invasion, and strikingly increased the protein expression of VCAM-1. Silencing of Smad3 abated TGF-β1-stimulated VCAM-1 expression. Furthermore, the promoting effects of TGF-β1 on the proliferation, migration, and invasion of endometriotic cyst stromal cells were blocked by silencing of VCAM-1. Conclusion Knockdown of VCAM-1 impedes TGF-β1-mediated proliferation, migration, and invasion of endometrial cells, thereby indicating that VCAM-1 may serve as a therapeutic target for endometriosis.